Nutrient Deprivation Mobilizes the Production of Unique Tocopherols as a Stress-Promoting Response in a New Indigenous Isolate Monoraphidium sp. - Singh, Rabinder; Paliwal, Chetan; Nesamma, Asha A.; Narula, Alka; Jutur, Pannaga P. (Frontiers in Marine Science, 2020)
The economic feasibility of the next generation algal biofuels rely largely on the simultaneous production of high-value added bioproducts (HVABs) in these photosynthetic cell factories. In this study, a newly isolated indigenous microalga belonging to ‎selenastraceae family Monoraphidium sp. (designated as CABeR41) has been isolated and characterized for their relevant biofuel precursors along with other HVABs i.e., tocopherols. Our preliminary datasets demonstrates accumulation of higher amounts of lipids (266.6 mg g-1dcw) along with anti-oxidant molecules such as α- and δ-tocopherols (456 µg g-1 dcw and 974 µg g-1 dcw) simultaneously, when subjected to nutrient deprivation. The total tocopherol content has been increased in nitrogen deplete conditions to 1450.24 µg g-1 dcw from 638.2 µg g-1 dcw. In conclusion, bioprospecting of new isolates from natural habitats and fine tuning of specific conditions without compromising growth will have potential for developing into an sustainable industrial strain for concomitantly production of biofuels and bioproducts.